THARȊQAT MUNᾹQASYAT AL FIRQAH AL SHAGȊRAH WA TANFȊZUHᾹ FI TA’LȊM AL NAHWI BI MA’HAD DᾹR AL FALᾹH SEMARANG - Ismah, Nur; Maghfurin, Ahmad (STIQ Amuntai, 2022)
Many studies show a strong relationship between teaching methods and student learning outcomes. For example, two well-known methods used to teach Arabic books in the Indonesian Pesantren are Bandongan and Sorogan. However, teaching grammar at Pesantren Dār al Falāh Semaranguses a different small group discussion method. This research seeks to examine the effectiveness of its application. This is field research using observation, interviews, and documentation. Triangulation of sources, methods, and extended times have been relied on to verify the authenticity of the data. We concluded that the application of the small group discussion was in the stages of preparation, process, and evaluation. Nevertheless, the application of this method for teaching grammar has more advantages than shortcomings, and it is fit to be used. The helpful factors are the teacher's excellent preparation, students' willingness to study the subject they will discuss within the classroom, their enthusiasm in the discussion, and the teacher's explanation at the end of the class to strengthen the understanding of the students. The obstacles are limited academic time, and the presence of students who do not have sufficient knowledge of the subject studied, leading to their lack of participation in the discussion.